Low Cost Cassava Production Strategy through Nutrient Use Efficient Genotypes Integrated with Low Input Management - S. U, Shanida Beegum (JOURNAL OF ROOT CROPS, 2016)
Abstract Nutrient use efficient (NUE) genotypes and low input nutrient management practices are becoming important due to escalating fertilizer prices and its hazardous impact on environment. Hence, the present study was aimed at testing the possibility of integrating NUE genotypes and low cost soil fertility management practices in reducing the quantity of inputs so as to generate an economically feasible and environmentally sustainable management practice in cassava. Having been understood the superiority of NUE genotypes under low input management under controlled condition in cassava, field experiments were conducted for two years (2012-2014) in a split plot design with three NPK efficient genotypes as main plot treatments and four nutrient management practices as subplot treatments. NPK efficient genotypes (Acc. No. 905 and 906) under low input management practice (green manuring in situ with cowpea as organic manure source + STBF (major + secondary + micronutrients) + nutrient efficient bio fertilizers) was found promising in terms of tuber yield and B: C ratio and the low input strategy could save P, K, Mg and Zn to the tune of 100, 11.5, 62.5 and 80% respectively. The percentage increase in input cost under the other practices over the low input practice varied significantly up to 55%.